Is Oxybutynin Treatment as Effective as Surgery in Palmar and Axillary Hyperhidrosis? - Celal Buğra Sezen; Süleyman Anıl Akboğa; Anar Süleymanov; Anıl Gökçe; Ali Çelik; İsmail Cüneyt Kurul (Haseki Tıp Bülteni)
Aim: Our aim in this study was to evaluate the surgical treatment of hyperhidrosis versus oxybutynin medical treatment comparing the response and long-term complications. Methods: We evaluated medical and surgical treatment results of 56 palmar and axillary hyperhidrosis patients (29 female, 27 male). Patients mean age was 26.6±6.3 (minimum: 18 - maximum: 48) years old. Sympathetic ganglion ligation was performed in patients treated with surgery.In patients we used medical treatment, oxibutinin treatment was started at 2.5 mg/day and the doses of the drug were increased according to the treatment response. The quality of life index implemented by Amir was adapted into Turkish and used for evaluating life quality of the patients in the study. Results: Postoperative the quality of life scores of palmar hyperhidrosis patients were found to be higher in T3-T4 levels than in T2-T3-T4 levels (p=0.015). In patients with axillary hyperhidrosis, there was no difference between T2-T3-T4 and T4-T5 level surgical operations (p>0.05). The average the quality of life score of patients who received medical treatment was 28.54±5.74. There was no significant difference in the quality of life scores between patients treated with surgery and medical therapy with oxybutynin. Conclusion: We assume that the response rates to oxybutynin are as favorable as surgery in the treatment of hyperhidrosis.